Re-envisioning Emergency Food Systems Using Photovoice and Concept Mapping. (January 2021) - Shannon, Jerry; Borron, Abigail; Kurtz, Hilda; Weaver, Alexis
Researchers engaging in participatory planning initiatives can enhance participant involvement by using concept mapping integrated with photo-elicitation. Focusing on a research collaboration between the University of Georgia and the Atlanta Community Food Bank, our research used these methods to identify sources of instability for food insecure households and generate new program ideas. Our results underscore clients' capacity for procuring food and providing input on pantry policies. The productive conversations facilitated through this process also demonstrate the need for stronger communication between pantry staff and clientele. This article makes a unique contribution to mixed methods research by demonstrating how an integrative research design can support communities of inquiry and participatory research that identifies obstacles faced by low-income households.